African dust deposition in Puerto Rico: Analysis of a 20-year rainfall chemistry record and comparison with models. (1st November 2019) - McClintock, M.A.; McDowell, W.H.; González, G.; Schulz, Michael; Pett-Ridge, J.C.
Abstract: Dust deposition represents an important flux of rock-derived nutrients such as phosphorus to ecosystems on highly weathered soils. Direct measurements of terrestrial dust deposition and its spatial variability are rare, yet they are essential for testing models of dust deposition processes and understanding the biogeochemical effects of dust. Long-term records of precipitation chemistry are available in the Luquillo Mountains of Puerto Rico, which are downwind of the world's largest dust source in Africa. We analyzed 20-year datasets of openfall, throughfall, and wet-only precipitation chemistry with weekly resolution at two different locations in the Luquillo Mountains to evaluate spatial and temporal variability of dust inputs and compare the observational records with models. Based on rainwater dissolved silica and total suspended solids content, the measured dust flux varied by a factor of 2 over a distance of 10 km despite similarities between sites in elevation and rainfall amount. In comparison with simulated dust deposition from ten models in the Aerosol Comparisons between Observations and Models (AeroCom) project, the empirical rainfall chemistry agrees well with the mean of the models on the seasonal distribution of wet dust distribution. Both the data and the models show a summer maximum in wet dust deposition that is consistent with variation in transport pathways and the dust source area emission strength based on environmental conditions in the Sahel region. The rainfall chemistry record and AeroCom models also agree in terms of attributing ~70% of the total dust deposition overall to dry deposition, although the range of uncertainty in the models is large. The results indicate value in combining long-term analysis of rainfall chemistry with data from satellites and models, and highlight the need for accurate ground-based metrics for dry deposition to improve understanding and modeling of dust deposition processes. The dataset complements earlier studies that characterize the dust plume originating from Northern Africa and its impact on ecosystems in South America and the Caribbean. Highlights: >50% of total dust deposition in the Luquillo Mountains occurs as dry deposition. Rainfall chemistry records and models agree on seasonality of wet dust deposition. Dust deposition is highly spatially variable on 10 km landscape scale.